(untitled) (European Bison Conservation Newsletter, 2008)
The aim of the study was the determination of the calcium status in various tissues (liver, kidney, rib, muscle, hoof and hair) of European bison from free living herd in the Białowiez˙a Primeval Forest. The material was obtained in the winter 2002 from 20 animals of both sexes, aged from 5 months to 5 years, eliminated from the herd. Animals were grouped according to sex (males – females), and age (calves up to one year– animals over two years). The mean calcium content in various tissues was as follows: – liver: 288.6±108.1; females 295.4±105.4; males 272.8±122.7; calves 280.6±96.0; over 2 years 312.6±149.2 [mg/kg fresh tissue], – kidney: 412.9±78.3; females 418.2±89.0; males 401.5±52.8; calves 416.8±73.6; over 2 years 402.2±98.8 [mg/kg fresh tissue], – rib: 170.9±23.2; females 166.4±17.8; males 180.8 ±31.6; calves 168.0±24.5; over 2 years 179.0±18.0 [mg/kg fresh tissue], – muscle: 388.3±227.7; females 423.3±274.8; males 318.3±37.3; calves310.9±82.3; over 2 years 659.3±372.3 [mg/kg fresh tissue], – hoof: 1113.1±239.0; females1044.3±118.7; males1216.2±340.8; calves1162.0±280.2; over 2 years1015.0±73.0 [mg/kg dry matter]; – hair: 953.9±221.4; females 881.4±238.3; males 1071.6±131.1; calves 973.9±199.3; over 2 years 903.7±284.1 [mg/kg air dry matter]. – Except muscles, no statistically significant differences in the calcium content in bison tissues, depending on the sex and age, were observed.